A systematic review of patient-reported outcome measures (PROMs) in cystic fibrosis. Issue 10 (1st October 2020) - Ratnayake, Irushi; Ahern, Susannah; Ruseckaite, Rasa
Abstract : Background: To determine patient-reported outcome measures (PROMs) which may be suitable for incorporation into the Australian Cystic Fibrosis Data Registry (ACFDR) by identifying PROMs administered in adult and paediatric cystic fibrosis (CF) populations in the last decade. Methods: We searched MEDLINE, EMBASE, Scopus, CINAHL, PsycINFO and Cochrane Library databases for studies published between January 2009 and February 2019 describing the use of PROMs to measure health-related quality of life (HRQoL) in adult and paediatric patients with CF. Validation studies, observational studies and qualitative studies were included. The search was conducted on 13 February 2019. The COnsensus-based Standards for the selection of health Measurement INstruments Risk of Bias Checklist was used to assess the methodological quality of included studies. Results: Twenty-seven different PROMs were identified. The most commonly used PROMs were designed specifically for CF. Equal numbers of studies were conducted on adult (32%, n=31), paediatric (35%, n=34) and both (27%, n=26) populations. No PROMs were used within a clinical registry setting previously. The two most widely used PROMs, the Cystic Fibrosis Questionnaire—Revised (CFQ-R) and the Cystic Fibrosis Quality of Life Questionnaire (CFQoL), demonstrated good psychometric properties and acceptability in English-speaking populations. Discussion: We found that although PROMs are widely used in CF, there is a lack of reporting on the efficacy of methods and timepoints of administration. We identified the CFQ-R and CFQoL as the most suitable for incorporation in the ACFDR as they captured significant effects of CF on HRQoL and were reliable and valid in CF populations. These PROMs will be used in a further qualitative study assessing patients' with CF and clinicians' perspectives toward the acceptability and feasibility of incorporating a PROM in the ACFDR. PROSPERO registration number: CRD42019126931.